Importance of crop phenological stages for the efficient use of PGPR inoculants - Alexandra Stoll (Nature Portfolio, 2021)
Abstract During the last decades, the incorporation of beneficial microorganisms in agriculture crop management has become a common practice. Seed coating of these microorganisms still faces technical issues, which limit its implementation in conventional agriculture. An adaption to widely established agricultural practices, e.g. fertigation, could help to overcome these issues. Here, using Bacillus velezensis strain BBC047, we show the influence of the crop phenological stages on the efficiency and success of microbial inoculation under agricultural conditions. In the commercial nursery, strain BBC047 improved growth in a variety of horticulture crops like basil, cabbage, tomato and bell pepper, the latter with the strongest effects in strengthening and accelerating the seedling growth (root and aerial biomass). For a field trial under productive conditions, different application strategies were compared, using bell pepper (Capsicum annuum L.) as crop under fertigation: conventional management (T1), application to the seedling (only nursery, T2), only post-transplant application (field, T3) and a combination of both (T4). In T2 and T4, the post-transplantation survival rate (p < 0.05) improved and the productivity of the plants increased (> 100%). Applications of BBC047 post-transplantation (T3) caused a lower increase in productivity (25%). Fruits from all three application strategies contained significantly more Vitamin C. We conclude that in conventional agriculture, the applications of PGPR inoculants to early crop phenological stages like nurseries are a viable alternative for the efficient use of PGPR inoculants. In comparison, a late introduction of a PGPR reduces its beneficial effect on crop productivity. We highlight that an appropriate timing in the use of PGPR inoculants is crucial for product development and success in sustainable agriculture.